Resposta :
Aqui basta aplicar as propriedades da potenciação:
i = (a . b)ⁿ = aⁿ . bⁿ
ii = Xᵃ . Xᵇ = Xᵃ⁺ᵇ
iii = Yᵃ ÷ Yᵇ = Yᵃ⁻ᵇ
Com isso o problema fica resumido a
[(3 . 10)¹⁰ . (2 . 7)¹¹ . (2 . 3)¹²] ÷ [(2 . 3 . 7)²¹] = 2² . 3 = 12
![Ver imagem TOMSON1975](https://pt-static.z-dn.net/files/d27/b742d8b527a5b7bff9f7724b146abd7e.png)
Aqui basta aplicar as propriedades da potenciação:
i = (a . b)ⁿ = aⁿ . bⁿ
ii = Xᵃ . Xᵇ = Xᵃ⁺ᵇ
iii = Yᵃ ÷ Yᵇ = Yᵃ⁻ᵇ
Com isso o problema fica resumido a
[(3 . 10)¹⁰ . (2 . 7)¹¹ . (2 . 3)¹²] ÷ [(2 . 3 . 7)²¹] = 2² . 3 = 12